2017
DOI: 10.1590/1980-5373-mr-2017-0102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron Beam and Gamma Rays on Carbon Nanotube Yarn Structure

Abstract: Individual carbon nanotubes (CNTs) exhibit excellent mechanical, electrical and thermal properties, leading to development of a new generation of advanced lightweight materials and spacecraft electronics substituting the electronics based on silicon. The direct assembly of CNTs into macroscopic fibers or sheets has been a way to overcome their dispersion and processing challenges. Because of a wide range of applications of this material, we investigate effectively the defects on CNT yarns structures created by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…10,11,17,19 In addition, it was also reported that γ-irradiation of CNTs resulted in a reduced tube diameter and reduced empty inter-wall spaces. 10,19,20…”
Section: Resultsmentioning
confidence: 96%
“…10,11,17,19 In addition, it was also reported that γ-irradiation of CNTs resulted in a reduced tube diameter and reduced empty inter-wall spaces. 10,19,20…”
Section: Resultsmentioning
confidence: 96%
“…These results indicate that after electron beam irradiation or after thermal shock, the structure of graphite has been self-assembled better than that of the untreated samples; moreover, the combination of EB irradiation and then thermal shock of graphite samples were obtained in the sample EG10-120 with less defect structure than EG0. In addition, the 2D peak position of the sample is shifted to the position with a lower wave number than G0, indicating a decrease in the number of layers or expansion in the graphite structure after irradiation or heat shock [5,13,[15][16][17].…”
Section: Raman Spectramentioning
confidence: 99%
“…Expansion graphite has been studied and fabricated by many different methods such as using chemical agents inserting graphite structure and then thermal shock at high temperature [6,[11][12][13] or by microwave [4,14]. In addition, direct treatment of graphite by ionizing radiation (gamma rays, electron beams...) to change the structure was also studied [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently a fast surface diffusion of knocked-out C atoms proceeds very fast in the vacancies places (vacancy annealing) [4]. The atoms, which are knocked out of the graphene plane or ultrathin crystal under action of high-energy (1 MeV-1 GeV) ions [5][6][7], electrons (see [6,[8][9][10] and references therein), protons and positrons (see [6,11] and references therein), cannot escape from the graphene plane to enter the deep bulk region. Emerging in beta-rays-,ions-irradiated graphene the radiation vacancies form clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging in beta-rays-,ions-irradiated graphene the radiation vacancies form clusters. [8,12,13] The vacancies are neutral, but they host a positively charge by applying electromagnetic pulses [13].…”
Section: Introductionmentioning
confidence: 99%